Between Nationalist and Cosmopolitan Visions of Fraternity. The Prefigurative Role of the French Revolution in Victor Hugo’s introduction to «Paris guide» (1867) and Robert Hamerling’s «Danton und Robespierre» (1871) (Studia austriaca, 2023)
This article analyses the ways in which fraternity is imagined in Victor Hugo’s introductory essay to Paris guide (1867) and Danton und Robespierre (1871), by the Austrian poet Robert Hamerling. Both texts use the French Revolution as a pretext to articulate a cosmopolitan vision that has to be understood as a reaction to the political tensions in the prelude to and aftermath of the Franco-Prussian War (1870-71). By reconstructing how Hugo and Hamerling intervene in a broader debate on the question of nationalism and internationalism, this article sheds more light on how literature was a vehicle for cosmopolitan views.